Barriers, Threats and Determinants of e-Government Development based on the Example of Poland - Adam MAKOWSKI; Jacek BUKO (Communications of International Proceedings, 2021)
Referred to as e-services, e-government services are intrinsically connected with remote provision of services over the Internet. As the services are automated, their implementation requires necessary organisational changes, new abilities of public authorities and citizens. The purpose of this paper is to analyse the key barriers, threats and determinants of e-government services development based on the example of Poland. The primary research methods applied hereinafter include: critical review of available sources and literature on the subject, synthesis and generalisation. Results of the analyses performed suggest high development potential, but also numerous threats to functioning of this area of administration. In Polish conditions, popularisation of e-administration requires involvement of the state in building the information and communications technology (ICT) infrastructure, increasing its efficiency, usability and security, conducting education of citizens in the area of information technology and counteracting the threats of cybercrime and corruption.
Keywords: E-Government; E-Administration; Cybercrime; Corruption